2019
DOI: 10.1002/ldr.3478
|View full text |Cite
|
Sign up to set email alerts
|

The effects of forestry and agroforestry plantations on bird diversity: A global synthesis

Abstract: The increasing expansion of productive lands around the world during the last decades constitutes a strong driver of biodiversity loss, as they are usually established near to high diversity areas. Despite many studies that have compared bird diversity between natural and productive systems, a global synthesis is still missing and important for understanding how biodiversity is being altered. We conducted a meta‐analysis based on 144 case studies to assess the effects of four types of plantations (forestry, oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 66 publications
1
29
0
Order By: Relevance
“…Declining strict forest-dwelling species at a regional scale is widely associated with human disruption to habitats that reduce the space occupied by and affect the foraging grounds of a diverse set of species (Brooks et al 1999;Renjifo 2001). Global meta-analyses showed that bird species richness and abundance were particularly susceptible to decline in areas with low structural heterogeneity such as plantations and farmland conversions (Bohada-Murillo et al 2020). The continuous conversion within or near intact habitats for agricultural expansions during the last decades has driven high biodiversity loss in many hotspot regions including the Philippines (Brooks et al 2002).…”
Section: Body Mass (Kg)mentioning
confidence: 99%
“…Declining strict forest-dwelling species at a regional scale is widely associated with human disruption to habitats that reduce the space occupied by and affect the foraging grounds of a diverse set of species (Brooks et al 1999;Renjifo 2001). Global meta-analyses showed that bird species richness and abundance were particularly susceptible to decline in areas with low structural heterogeneity such as plantations and farmland conversions (Bohada-Murillo et al 2020). The continuous conversion within or near intact habitats for agricultural expansions during the last decades has driven high biodiversity loss in many hotspot regions including the Philippines (Brooks et al 2002).…”
Section: Body Mass (Kg)mentioning
confidence: 99%
“…4). For example, the Brazilian Atlantic rainforest, the Indian peninsula, and the south-east Asia archipelago have the largest proportions of threatened birds, but protected areas are negligible at those locations (Peh et al, 2006;Barlow et al, 2007;Bohada-Murillo et al, 2020). A similar pattern is observed for mammals of south-east Asia and amphibians of eastern China.…”
Section: Discussionmentioning
confidence: 64%
“…If we examine this pattern at the global scale, we observe a moderate correspondence of protected areas with biodiversity hotspots (Figure 3), which is even lower when we examine threatened species instead (Figure 4). For example, the Brazilian Atlantic Rainforest, the Indian Peninsula, and the Southeast Asian archipelago have the largest proportions of threatened birds, but protected areas are negligible at those locations [44][45][46]. A similar pattern is observed for mammals of Southeast Asia and amphibians of Eastern China.…”
Section: Discussionmentioning
confidence: 64%